?EFFECTS OF SULPHUR, ZINC AND BORON ON YIELD, YIELD COMPONENTS AND NUTRIENT UPTAKE OF WHEAT - Islam, M R; Islam, M S; Iahiruddin, M; Hoque, M S (Biological Sciences - PJSIR, 1999)
A field experiment was carried out in an alluvial soil of Bangladesh to study the effect of S, Zn and B on yield, yield components and nutrient uptake by wheat (cv. Kanchan), There were eight treatments consisting of control, S, Zn, B, S+Zn, S+B, Zn+B and S+Zn+B. The ratesof application of S,Zn andB were 20,4 and 3 kg ha' in the form of gypsum, zincoxideandboricacid,respectively.Basaldosesof 100kgNha' asurea,60kgPP5 ha' asTSP and40kg Kp ha' from muriate of potash were applied to all plots. The experiment was carried out in randomized block design with four replications.The application ofS,Zn andBsignificantlyincreasedplantheight,effectivetillerspalnt', spikelength, grain spike", 1000-grain weight and grain and straw yields of wheat. The effect of S was dominant in increasing grain yield followed by Band Zn applications. The highest grain yield of 25.82 q ha' was obtained when S, Zn and B were applied together which was42% higherovercontrol.Nutrientanalysisofgrainandstrawindicatedthat S,Zn andBcontents were significantly influenced by the treatments. The content of S,Zn andB in grain was higher when a particular nutrient was applied. Thus, for efficient wheat production in this soil, application of S, Zn and B is essential.